Trig please help!
posted by hayden on .
sin^6 x + cos^6 x=1  (3/4)sin^2 2x
work on one side only!

LS looks like the sum of cubes
sin^6 x + cos^6 x
= (sin^2x)^3 + (cos^2x)^3
= (sin^2x+cos^2x)(sin^4x  (sin^2x)(cos^2x) + sin^4x)
= (1)(sin^4x  (sin^2x)(cos^2x) + sin^4x)
Now let's do some "aside"
(sin^2x + cos^2)^2 would be
sin^4x + 2(sin^2x)(cos^2x) + cos^4x
we 'almost' have that above, differing only by the coefficient of the middle term. We can fix that by saying
(sin^4x  (sin^2x)(cos^2x) + sin^4x)
= sin^4x + 2(sin^2x)(cos^2x) + cos^4x  4(sin^2x)(cos^2x)
= (sin^2x + cos^2x)  3(sin^2x)(cos^2x)
= 1  3(sin^2x)(cos^2x)
almost there!
recall sin 2A = 2(sinA)(cosA)
so 3(sin^2x)(cos^2x)
= 3(sinxcosx)^2
= 3((1/2)sin 2x)^2
= (3/4)sin^2 2x
so
1  3(sin^2x)(cos^2x)
= 1  (3/4)sin^2 2x
= RS !!!!!!
Q.E.D. 
(sin^2x+cos^2x)(sin^4x  (sin^2x)(cos^2x) + sin^4x) I DON'T AGREE WITH THIS
SHOULDNT IT BE
(sin^2x+cos^2x)(sin^4x  (sin^2x)(cos^2x) + COS^4 X ??